Sexual congruency in the connectome and translatome of VTA dopamine neurons - Chung, Amanda S. (Sci Rep, 2017)
The ventral tegmental area (VTA) dopamine system is important for reward, motivation, emotion, learning, and memory. Dysfunctions in the dopamine system are linked to multiple neurological and neuropsychiatric disorders, many of which present with sex differences. Little is known about the extent of heterogeneity in the basic organization of VTA dopamine neurons with regard to sex. Here, we characterized the cell-specific connectivity of VTA dopamine neurons, their mRNA translational profile, and basic electrophysiological characteristics in a common strain of mice. We found no major differences in these metrics, except for differential expression of a Y-chromosome associated mRNA transcript, Eif2s3y, and the X-linked, X-inactivation transcript Xist. Of note, Xist transcript was significantly enriched in dopamine neurons, suggesting tight regulation of X-linked gene expression to ensure sexual congruency. These data indicate that the features that make dopamine neurons unique are highly concordant and not a principal source of sexual dimorphism.